Automated TUNEL assay on tissue sections via robotics. (2nd April 2016) - Biswas, Sabyasachi; Yaylaoglu, Murat B.; Safra, Noa; Arceo, Rommel; Taylor, Robin E.; Eastham-Anderson, Jeffrey; Foreman, Oded
Abstract : The manual TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling) method for detecting deoxyribonucleic acid (DNA) fragmentation during apoptosis is widely used to determine cell death in tissue sections. However, manually staining large numbers of slides is cumbersome and may result in inconsistent signal intensities. We have developed a simple automated TUNEL assay using a robotic platform and a popular apoptosis detection kit. Comparing manual and automatic staining methods of serially sectioned murine tissue blocks showed no differences in quality or quantity of signal. The automated TUNEL assay allows larger throughput and provides consistent results across many tissue types.